Levels of Management and Economic Performance of Companies - Tokarski Stefan; Tokarski Krzysztof; Sikora Joanna (Management, 2016)
In order to achieve competitive results, the manager must master the skills necessary for subsequent levels of management. In the present study we have verified three hypotheses regarding the correlation between the level of control and efficiency, a form of ownership and influence on the managing level to direct and indirect subordinates. Two of the hypotheses gained the expected level of significance and the third was statistically insignificant.